Climate migration and its impact on sustainable development in the mountain and western coast regions - Saad Saleh Amer Al-Hajj (AlQalam Journal of Medical and Applied Sciences, 2024)
The research aims, through the descriptive and photographic approach, to study climate migration and its impact on sustainable development in the regions of the Mountain and the West Coast. It has reached a number of results that can be summarized in the following points: 1- Climate change is no longer of interest to specialists in meteorology and geography, and as a result of its global impacts, it has become a matter of interest for many applied, social, political, and economic sciences, etc. 2- Climate migration is one of the most important aspects of the twenty-first century, as a result of the world’s exposure to climate changes resulting from rising temperatures and global warming, which in turn has led to desertification and drought, increased natural disasters, decreased agricultural and animal production, and increased health, social and economic risks, and has become a threat to sustainable development in the Western Mountain region. 3- The clear impact of climate change on the inhabitants of the Western Mountain, as desertification, drought, water shortages, harsh climate, and thoughts of migration and departure towards the West Coast have spread. 4- As a result of climate change and climate migration, agricultural lands that constitute the natural resources of the Western Mountain region have been exposed to erosion and desertification. Olive, almond and fig trees that depend on seasonal rains and have been widespread in the Western Mountain region for several decades have also been damaged and neglected, which in turn negatively affects food security. 5- As a result of climate migration from mountainous areas to the Western Coast regions, many residential subdivisions have emerged and agricultural lands have been divided into small subdivisions, which in turn negatively affects sustainable development and the rights of future generations. 6- As a result of climate migration from mountainous areas to the Western Coast regions and the spread of random residential areas without planning and the exploitation and depletion of groundwater resources, which in turn affects water security. 7- Most of the inhabitants of the Western Mountain practice rain-fed agriculture that depends on seasonal rains, as well as raising sheep and camels in open desert pastures, which in turn has been affected by climate change and the exposure of lands to drought, and climate migration from the mountain to the coast, which negatively affects the future of these two activities and the culture of future generations. يهدف البحثُ من خلال المنهج الوصفي والفوتوغرافي إلى دراسة الهجرة المناخية وتأثيرها على التنمية المستدامة بمنطقتي الجبل والساحل الغربي، وقد توصل إلى عدد من النتائج يمكن اختصارها في النقاط الآتية:1- لم يعد التغير المناخي من ضمن اهتمام المتخصصين بعلوم الأرصاد والجغرافيا، ونتيجة لتأثيراته العالمية أصبح محل اهتمام للعديد من العلوم التطبيقية والاجتماعية والسياسية والاقتصادية.. إلخ. 2- تعدَ الهجرة المناخية من أهم مظاهر القرن الحادي والعشرين، نتيجة لتعرض العالم للتغيرات المناخية الناتجة عن ارتفاع درجات الحرارة والاحتباس الحراري، الّذي بدوره أدّى إلى التصحر والجفاف، وازدياد الكوارث الطبيعية، وتراجع الإنتاج الزراعي والحيواني، وتزايد المخاطر الصحية والاجتماعية والاقتصادية، وأصبحت خطر يهدد التنمية المستدامة بمنطقة الجبل الغربي. 3- التأثير الواضح للتغير المناخي على سكان الجبل الغربي، حيث انتشر التصحر والجفاف ونقص مخزون المياه، وقسوة المناخ، والتفكير في الهجرة، والمغادرة اتجاه الساحل الغربي. 4- نتيجة للتغير المناخي والهجرة المناخية تعرضت الأراضي الزراعية الّتي تشكّل الموارد الطبيعية لمنطقة الجبل الغربي للانجراف والتصحّر، كما تعرضت أشجار الزيتون واللوز والتين الّتي تعتمد على الأمطار الموسمية والّتي تنتشر بمنطقة الجبل الغربي منذ عدة عقود للتلف وعدم الاهتمام وهذا بدوره يؤثر سلباً على الأمن الغذائي. 5- نتيجة للهجرة المناخية من المناطق الجبلية إلى مناطق الساحل الغربي ظهرت كثير من المقسمات السكنية وتقسيم الأراضي الزراعية إلى مقسمات صغيرة وهذا بدوره يؤثر سلباً على التنمية المستدامة وحقوق للأجيال القادمة. 6- نتيجة للهجرة المناخية من مناطق الجبل إلى مناطق الساحل الغربي وانتشار المناطق السكانية العشوائية دون تخطيط واستغلال الموارد المائية الجوفية واستنزافها وهذا بدوره يؤثر الأمن المائي . 7- يمارس أغلب سكان الجبل الغربي نشاط الزراعة البعلية الّتي تعتمد على الأمطار الموسمية، وكذلك نشاط تربية الأغنام والإبل بالمراعي المفتوحة الصحراوية، وهذا تأثر بدوره بالتغير المناخي وتعرض الأراضي للجفاف، والهجرة المناخية من الجبل إلى الساحل وهذا يؤثر سلباً على مستقبل هذين النشاطين وثقافة الأجيال القادمة.